4u-13=9(u+3)

Simple and best practice solution for 4u-13=9(u+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4u-13=9(u+3) equation:


Simplifying
4u + -13 = 9(u + 3)

Reorder the terms:
-13 + 4u = 9(u + 3)

Reorder the terms:
-13 + 4u = 9(3 + u)
-13 + 4u = (3 * 9 + u * 9)
-13 + 4u = (27 + 9u)

Solving
-13 + 4u = 27 + 9u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-9u' to each side of the equation.
-13 + 4u + -9u = 27 + 9u + -9u

Combine like terms: 4u + -9u = -5u
-13 + -5u = 27 + 9u + -9u

Combine like terms: 9u + -9u = 0
-13 + -5u = 27 + 0
-13 + -5u = 27

Add '13' to each side of the equation.
-13 + 13 + -5u = 27 + 13

Combine like terms: -13 + 13 = 0
0 + -5u = 27 + 13
-5u = 27 + 13

Combine like terms: 27 + 13 = 40
-5u = 40

Divide each side by '-5'.
u = -8

Simplifying
u = -8

See similar equations:

| 9(1-3b)-8b= | | 29=2v-11 | | ?3k+10=k+2 | | 3x17/5= | | 5(8x+2)+10x= | | -x/6=2x=52 | | w/2-15=13 | | 202+(-16y)=2.615384615+0.615384614y | | 2=64x | | 10+6(v-4)= | | 2x^2+2.5x-1=0 | | 7v=-25 | | ?9r=20+r | | 5(6y-4)=20y | | y^7-2x^7y^5=10 | | -5.5(2p+5)-2.7(3p-6)= | | -3=-28y | | vf=vi+atforvi | | 23-4x=26 | | 45=-y/7 | | 10x-20=-20 | | cos(2x-pi/4)=-(sqrt(2))/2 | | 8x=8(x+12) | | (2b-4)(b+2)= | | -w/4=-60 | | 18x-25x=14 | | tan^-1(350/x) | | -12x+4=-44 | | (3x-5y)+4y= | | 1.7j=2.21 | | -3-(3-3p)= | | 9x^2+15x+9=0 |

Equations solver categories